Influence of the Camera Viewpoint on Augmented Reality Interaction - Taira, Gabriel Mamoru Nakamura; Sementille, Antonio Carlos [UNESP]; Sanches, Silvio Ricardo Rodrigues (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Many Augmented Reality (AR) applications run on conventional platforms such as desktops or laptops. Desktop applications usually display the 3D environment through a 2D screen while an external webcam attached to the computer performs the capture of the scene. In these applications, the camera viewpoint is an important factor since it can facilitate or hinder accuracy in tasks performed. The objective of this research is to find the optimal camera viewpoint for a desktop AR environment.
Keywords: Augmented Reality; Camera Viewpoint; User Perception